Inside Cover: Structural and Mechanistic Studies on Substrate and Stereoselectivity of the Indole Monooxygenase VpIndA1: New Avenues for Biocatalytic Epoxidations and Sulfoxidations (Angew. Chem. Int. Ed. 17/2023). Issue 17 (15th March 2023) - Kratky, Julia; Eggerichs, Daniel; Heine, Thomas; Hofmann, Sarah; Sowa, Philipp; Weiße, Renato H.; Tischler, Dirk; Sträter, Norbert
Abstract : A flavin‐dependent group E monooxygenase ("GEM") has been characterized by crystal‐structure analysis, computational and kinetic studies to reveal substrate binding and mechanistic details for this class of enzymes for the first time. Based on these data, Dirk Tischler, Norbert Sträter, and co‐workers redesigned the substrate binding pocket to synthesize chiral epoxides and sulfoxides with high stereoselectivity, a true treasure of molecular gems, as described in their Research Article (e202300657) .